Spherical grating based x‐ray Talbot interferometry. Issue 11 (19th October 2015) - Cong, Wenxiang; Xi, Yan; Wang, Ge
Abstract : Purpose: Grating interferometry is a state‐of‐the‐art x‐ray imaging approach, which can acquire information on x‐ray attenuation, phase shift, and small‐angle scattering simultaneously. Phase‐contrast imaging and dark‐field imaging are very sensitive to microstructural variation and offers superior contrast resolution for biological soft tissues. However, a common x‐ray tube is a point‐like source. As a result, the popular planar grating imaging configuration seriously restricts the flux of photons and decreases the visibility of signals, yielding a limited field of view. The purpose of this study is to extend the planar x‐ray grating imaging theory and methods to a spherical grating scheme for a wider range of preclinical and clinical applications. Methods: A spherical grating matches the wave front of a point x‐ray source very well, allowing the perpendicular incidence of x‐rays on the grating to achieve a higher visibility over a larger field of view than the planer grating counterpart. A theoretical analysis of the Talbot effect for spherical grating imaging is proposed to establish a basic foundation for x‐ray spherical gratings interferometry. An efficient method of spherical grating imaging is also presented to extract attenuation, differential phase, and dark‐field images in the x‐ray spherical grating interferometer. Results: Talbot self‐imaging with spherical gratings is analyzed based on the Rayleigh–Sommerfeld diffraction formula, featuring a periodic angular distribution in a polar coordinate system. The Talbot distance is derived to reveal the Talbot self‐imaging pattern. Numerical simulation results show the self‐imaging phenomenon of a spherical grating interferometer, which is in agreement with the theoretical prediction. Conclusions: X‐ray Talbot interferometry with spherical gratings has a significant practical promise. Relative to planar grating imaging, spherical grating based x‐ray Talbot interferometry has a larger field of view and improves both signal visibility and dose utilization for pre‐clinical and clinical applications.